PENGARUH SUBSTITUSI TERIGU DENGAN TEPUNG BERAS MERAH (Oryza nivara) TERHADAP KARAKTERISTIK BAKPAO - Forsalina, Fiensa; Nocianitri, Komang Ayu; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 2 (2016): Jurnal ITEPA)
The research aims to investigate the effect of substitution wheat flour with brown rice flour to the characteristics of bakpao and determine the rate of its which produce the best characteristics of bakpao. The Completely Randomized Design used in this research with the comparisons of wheat flour with brown rice flour which consisted of 6 levels, such as 1) 100% : 0%, 2) 95% : 5%, 3) 90% : 10%, 4) 85% : 15%, 5) 80% : 20%, 6) 75% : 25% used as treatments. Each treatments was repeated 3 times to obtain 18 units. The datas were analyzed by analysis of variance. If there were any effect of the treatment, the analysis followed by Duncan's Multiple Range Test. The results showed that substitution of wheat flour with brown rice flour highly significant effect on the moisture content, antioxidant activity, crude fiber content, strength of expands, taste, color, flavor, texture and overall acceptance of bakpao. The best substitution of wheat flour with brown rice flour is 5% brown rice flour, with characteristics moisture content 31,55%, antioxidant activity 14,61%, crude fiber content 8,71%, strength of expands 55,81%, with criteria color 1,45 (white), texture 4,25 (soft), flavor 2,50 and taste 1,90 (not the typical brown rice) and overall acceptance of bakpao 5,70 ( mostly like).
Keywords: Wheat, Brown Rice Flour, Characteristics Bakpao, Substitutio